The almost last roundup - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2015)
Nobody on the ranch has seen a drought like the one this summer, ponds have dried up, the creek is down, and the cows are kicking up dust. Then there is a prairie fire. There is a desperate need for rain, and Pete the Barncat is trying to ruin Loper's birthday.